Derangement of body representation in complex regional pain syndrome: report of a case treated with mirror and prisms. - Bultitude, J; Rafal, R (2010)
Perhaps the most intriguing disorders of body representation are those that are not due to primary disease of brain tissue. Strange and sometimes painful phantom limb sensations can result from loss of afference to the brain; and Complex Regional Pain Syndrome (CRPS)-the subject of the current report-can follow limb trauma without pathology of either the central or peripheral nervous system. This enigmatic and vexing condition follows relatively minor trauma, and can result in enduring misery and a useless limb. It manifests as severe pain, autonomic dysfunction, motor disability and 'neglect-like' symptoms with distorted body representation. For this special issue on body representation we describe the case of a patient suffering from CRPS, including symptoms suggesting a distorted representation of the affected limb. We report contrasting effects of mirror box therapy, as well as a new treatment-prism adaptation therapy-that provided sustained pain relief and reduced disability. The benefits were contingent upon adapting with the affected limb. Other novel observations suggest that: (1) pain may be a consequence, not the cause, of a disturbance of body representation that gives rise to the syndrome; (2) immobilisation, not pain, may precipitate this reorganisation of somatomotor circuits in susceptible individuals; and (3) limitation of voluntary movement is neither due to pain nor to weakness but, rather, to derangement of body representation which renders certain postures from the repertoire of hand movements inaccessible.